Factors Associated With The Incidence Of Diarrhea In Toddlersin The Meureubo Health Center Working Area, Meureubo Sub-District, West Aceh District In 2023 - Muhammad Fassa; Fauzi Ali Amin; Anwar Arbi; Khairuman (PT. Anagata Sembagi Education, 2024)
Diarrhea is a potential endemic disease that can result in extraordinary outbreaks (KLB) and is often associated with mortality. According to data from the Meureubo Health Center in 2022, this center recorded the highest percentage of diarrhea cases among toddlers, reaching 67%. This study aims to examine the relationship between several factors clean water sources, latrine facilities, household waste management, wastewater disposal, maternal knowledge and education, nutritional status, personal hygiene, and environmental sanitation and the incidence of diarrhea in toddlers within the Meureubo Health Center working area, Meureubo District. This quantitative research utilizes a cross-sectional design and was conducted from May 13-29, 2023. The population includes all toddlers in the Meureubo Health Center working area, with a sample size of 97. Proportional random sampling was used to select the 97 respondents. Data were analyzed using the chi-square test with Stata 15, including univariate and bivariate analyses. The univariate results show that 43.30% of toddlers experienced diarrhea, 19.58% lacked access to clean water, 5.15% had inadequate latrine facilities, 57.73% faced insufficient household waste management, and 21.65% had improper wastewater disposal systems. Additionally, 30.93% of mothers had poor knowledge, 35.05% had a primary education level, 20.62% of toddlers were malnourished, and 39.18% had poor personal hygiene and environmental sanitation. Bivariate analysis reveals significant relationships between diarrhea incidence in toddlers and clean water sources (p-value: 0.0001), latrine facilities (p-value: 0.013), household waste management (p-value: 0.0001), wastewater disposal (p-value: 0.0001), maternal knowledge (p-value: 0.0001), maternal education (p-value: 0.036), nutritional status (p-value: 0.022), and personal hygiene and environmental sanitation (p-value: 0.0001). It is recommended that health workers, particularly those in health promotion, provide counseling on personal hygiene and environmental cleanliness